Physics and metaphysics in N. Losski's views - Obolevitch, Teresa (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2006)
Generally speaking, one can distinguish the following approaches to the question of the mutual relationship between physics and metaphysics: (1) both these domains are on equal footing, (2) physics is subordinated to metaphysics, (3) metaphysics is subordinated to physics. In the second half of the 19th century the fourth approach appears, namely an attempt to create a metaphysical system based on scientific results. The system created by the Russian philosopher N. Losski belongs to the latter category. In his view, the so-called substantial agents are fundamental building-blocks of the entire reality: from elementary particles to living organisms. Losski believed that his system could help solving some scientific problems. His ideas are similar to those of Leibniz and Whitehead.Generally speaking, one can distinguish the following approaches to the question of the mutual relationship between physics and metaphysics: (1) both these domains are on equal footing, (2) physics is subordinated to metaphysics, (3) metaphysics is subordinated to physics. In the second half of the 19th century the fourth approach appears, namely an attempt to create a metaphysical system based on scientific results. The system created by the Russian philosopher N. Losski belongs to the latter category. In his view, the so-called substantial agents are fundamental building-blocks of the entire reality: from elementary particles to living organisms. Losski believed that his system could help solving some scientific problems. His ideas are similar to those of Leibniz and Whitehead.